Modified urethrovesical anastomosis during robot-assisted simple prostatectomy: Technique and results - Castillo, Octavio (Prostate Int, 2016)
BACKGROUND: Despite significant developments in transurethral surgery for benign prostatic hyperplasia, simple prostatectomy remains an excellent option for patients with severely enlarged glands. The objective is to describe our results of robot-assisted simple prostatectomy (RASP) with a modified urethrovesical anastomosis (UVA). METHODS: From May 2011 to February 2014, RASP with UVA was performed in 34 patients by a single surgeon (O.C.) using the da Vinci S-HD surgical system. The UVA was performed between the bladder neck and urethral margin using the Van Velthoven technique. Demographic, perioperative, and outcome data were recorded. Complications were recorded with the Clavien–Dindo system. RESULTS: The mean (standard deviation) age was 68 years (62–74 years). The median preoperative prostate volume (interquartile range) was 117 cc (99–146 cc). Operative time was 96 minutes (78–126 minutes), estimate blood loss was 200 mL (100–300 mL), and two (5.8%) patients required a blood transfusion. No conversion to open surgery was needed. The median specimen weight on pathological examination was 76 g (58–100 g). The average hospital stay was 2.2 days (1–4 days) and average Foley catheter time was 4.6 days (4–6 days). No intraoperative complications were recorded. There were seven (20.5%) postoperative complications, most of them Clavien less than or equal to Grade II. CONCLUSION: The results of our study show that RASP with UVA is a feasible, secure, and reproducible procedure with low morbidity. Additional series with larger patient cohorts are needed to validate this approach.